SERVICE OPERATIONS MANAGEMENT FOR ENHANCING â€œHERITAGEâ€ EMOTIONS AT HOTEL SALAK, BOGOR - Hastjarjo Hastjarjo; Agus Prihanto; Nisa Rahmaniyah Utami (Jurnal Bisnis Manajemen, 2022)
We all know that a hotel must have a differentiation of service experience. But many hotels are historical buildings do not yet understand that they have a heritage competitive advantage, well. The "Heritage" hotel must improve the service profit chain with putting the 'heritage" to Customer Value (CV) equation: CVheritage = [Results + Process Quality (SQ) + Heritage Experience (HE)]/[Price + Cost]. This study focuses on the model choreography of a service delivery system to create and deliver a total embodied experience for customers. The model involves the choice of an operational strategy that consists of four areas: stageware (bricks and mortar), orgware (management systems), customerware (customer touch points), and linkware (system integration). The research question is "What improvements can be applied to improve the heritage customer experience at Hotel Salak Bogor". Novelty: This research is a best practice case study research in hotel service offering as strategic action that found â€œService Operations Management Model: SOMMâ€. Research Methods: This research is a single intrinsic case study at Hotel Salak Bogor as a bounded system in which an event, program or activity exists. This qualitative case study is designed to better understand the concept of service process management for the hotel. The research stages are (1) investigation of strategic process, (2) identification of customer variability and service offerings, (3) decision of operational strategy choices. Finding/Results: The model choreography can be used to integrate the business